Literature Review of Turn-Taking - Bingyang Shi (Journal of Linguistics and Communication Studies, 2023)
Turn-taking theory has attracted a lot of attention from linguistics and other disciplines since its emergence. Numerous studies have been conducted with regard to turn system, presenting its theory and empirical evolution in foreign and domestic research. In terms of turn-taking theory, majority of scholars state interpretation of its definition and rules without breaking through the framework of notion of Sacks. As far as application of turn-taking theory, they mainly focus on news interviews, TV programs, class interaction and daily dialogue and other aspects at home and abroad. Few studies concern about turn features of WeChat language and WeChat multiparty conversation. Through the view of turn and turn-taking, characteristics of WeChat multiparty conversation will be figured out and mechanism and characteristics of WeChat language will be summarized through the analysis of turn system of the WeChat multiparty conversation.